2013
DOI: 10.1177/1470320313475909
|View full text |Cite
|
Sign up to set email alerts
|

Circadian rhythm of urinary potassium excretion during treatment with an angiotensin receptor blocker

Abstract: Introduction:We have reported that the circadian rhythm of urinary potassium excretion (U K V) is determined by the rhythm of urinary sodium excretion (U Na V) in patients with chronic kidney disease (CKD). We also reported that treatment with an angiotensin receptor blocker (ARB) increased the U Na V during the daytime, and restored the non-dipper blood pressure (BP) rhythm into a dipper pattern. However, the circadian rhythm of U K V during ARB treatment has not been reported. Materials and methods: Circadia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 27 publications
0
9
0
Order By: Relevance
“…Na,K-ATPase is located in the basolateral side of DCTc, CNTc, and CDc, whereas H,K-ATPase is located in the apical or luminal side of Ic. The CNTc contains Na,K-ATPase and ROMK and is a key regulator of potassium by the kidney and the site of origin of kallikrein also influences urinary K + secretion [112]. Because hypertension is a very common illness induced by an unhealthy diet, altogether with aging are risk factors for Alzheimer's disease, another disease that might be influenced by a Na + /K + -ATPase defficient activity (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…Na,K-ATPase is located in the basolateral side of DCTc, CNTc, and CDc, whereas H,K-ATPase is located in the apical or luminal side of Ic. The CNTc contains Na,K-ATPase and ROMK and is a key regulator of potassium by the kidney and the site of origin of kallikrein also influences urinary K + secretion [112]. Because hypertension is a very common illness induced by an unhealthy diet, altogether with aging are risk factors for Alzheimer's disease, another disease that might be influenced by a Na + /K + -ATPase defficient activity (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…) of ENaC, independent of circulating aldosterone, and can decrease the U K V/U Na V ratio, indicating suppression of ENaC function (Ogiyama et al. ). In this way, ARBs can enhance daytime U Na V, similar to that achieved with diuretics (Fukuda et al.…”
Section: Discussionmentioning
confidence: 99%
“…In patients with CKD, ARBs decrease the urinary potassium (K) excretion rate (U K V) to U Na V ratio, indicating suppression of function of the epithelial sodium channel (ENaC) (Ogiyama et al. ). Previously, we reported that an increase in daytime U Na V in CKD patients can precede restoration of nondipper circadian BP rhythm within 2 days after the start of ARB treatment (acute phase) (Miura et al.…”
Section: Introductionmentioning
confidence: 99%
“…Attenuation of the TTKG by ARB treatment indicates decreased ENaC action in patients with chronic kidney disease (CKD). 4 …”
Section: To the Editormentioning
confidence: 99%